United Nations in combating the international crimes against humanity committed by the Islamic state of Iraq and the Levant in Yazidis and the military forces in Myanmar. - Borovskaya, Maria (Riga Graduate School of Law, 2019)
The most tragic contemporary cases related to the crimes against humanity are the Islamic State of Iraq and the Levant inhuman actions carried out against Yazidis Community and the Burmese military persecution operations against the Rohingya population. The international community was not ready to respond appropriately, but the consequences of the horrific events have to be eliminated. The further development of legal instruments and approaches depends on the prosecution of crimes against humanity provided by the United Nations.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; International criminal law